2016
DOI: 10.1088/0264-9381/33/20/205005
|View full text |Cite
|
Sign up to set email alerts
|

Black hole non-modal linear stability: the Schwarzschild (A)dS cases

Abstract: The nonmodal linear stability of the Schwarzschild black hole established in Phys. Rev. Lett. 112 (2014) 191101 is generalized to the case of a nonnegative cosmological constant Λ. Two gauge invariant combinations G± of perturbed scalars made out of the Weyl tensor and its first covariant derivative are found such that the map [) with domain the set of equivalent classes [h αβ ] under gauge transformations of solutions of the linearized Einstein's equation, is invertible. The way to reconstruct a representat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(77 citation statements)
references
References 42 publications
(184 reference statements)
3
74
0
Order By: Relevance
“…For example, generic spacelike singularities, traditionally regarded as being cosmological singularities, have been studied in detail [22]. It is also of interest to extend mathematical stability results to the case of a non-zero cosmological constant [9].…”
Section: Open Problems and Grmentioning
confidence: 99%
“…For example, generic spacelike singularities, traditionally regarded as being cosmological singularities, have been studied in detail [22]. It is also of interest to extend mathematical stability results to the case of a non-zero cosmological constant [9].…”
Section: Open Problems and Grmentioning
confidence: 99%
“…Consider now the zero boost weight case. Fields of this type turned out to be relevant recently for proving the nonmodal linear stability of the 4dimensional Schwarzschild (-de Sitter) black hole in [11,12]. The general case for the class of 4-dimensional Einstein type D spacetimes was analyzed in [4], where it was shown that the decoupling and field reconstruction results are only valid for the case of real Ψ 2 , static black holes being a particular case of this situation.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we analyze the l = 1 modes when ( n N, γ ij ) is a twodimensional round unit sphere. We follow the treatment of the Lorentzian case in [15], which requires only trivial modifications when addressing the Riemannian setting. We present the argument here because of the need of establishing estimates for the gauge vector fields.…”
Section: Appendix E the Asymptotics Of Vector Modesmentioning
confidence: 99%
“…According to [15,Section IV.A.2], it is convenient to define (X, Y a ) by solving the following system of equations:…”
Section: Appendix E the Asymptotics Of Vector Modesmentioning
confidence: 99%